Differentially expressed genes in head kidney of Pelteobagrus fulvidraco following Vibrio cholerae challenge - Jiang, Sen-Hao; Wu, Lin-Xin; Cai, Yu-Ting; Ma, Rui-Ting; Zhang, Hua-Bin; Zhang, Dai-Zhen; Tang, Bo-Ping; Liu, Qiu-Ning; Dai, Li-Shang (Frontiers in Immunology, 2023)
Yellow catfish (Pelteobagrus fulvidraco) is a freshwater fish with high economic value in eastern China. Nevertheless, pathogens causing bacterial diseases have brought about huge economic loss and high mortality in artificial aquaculture. For disease control, it is indispensable to further understand the immune system of Yellow catfish and its immune-related genes in which it responds to pathogenal infections. In this research, using high-throughput sequencing method analyze the transcriptomic spectrum of head kidney from P. fulvidraco challenged by Vibrio cholerae. Total 45,544 unique transcript fragments (unigenes) were acquired after assembly and annotation, with an average length of 1,373 bp. 674 differentially expressed genes (DEGs) were identified after the stimulation of V. cholerae, 353 and 321 genes were identified as remarkably up- or down-regulated, respectively. In order to farther study the immune-related DEGs, we performed KEGG enrichment and GO enrichment. The results showed gene response regulation of response to stimulus, immune response, immune system progress, to external stimulus and cellular response to stimulus. What the analysis of KEGG enrichment is significant to identify cheif immune related pathways. Real-time quantitative reverse transcription-PCR (qRT-PCR) results indicated that there are 10 immune response genes were found to be up-regulated compared to control group after 6 h of V. cholerae challenge. In summary, the results of our study are helpful to the defense mechanisms and immune system of yellow catfish in reation to bacterial challenge.